CERITA RAKYAT DI KECAMATAN 3 NAGARI KABUPATEN PASAMAN - Osniwati Osniwati (Jurnal Elektronik WACANA ETNIK, 2011)
Folktales have motive structure which contains and reflects the people who have it. Its necessary to documenting and archiving the folktales for next generations. This article describes the research result of documentation Kecamatan Tigo Nagari folktales. There are eleven folktales in Tigo Nagari. Nine of them are the people legend and three of them are . Those folktales are 1) Gunung Pasaman dan Talang Perindu, 2) Larangan menanam tebu, serai, kunyit, dan pisang, 3) Bukik Putuih, 4) Inyiak Durian Gunjo, 5) Aia angek di Malayu, 6) Lubuak Gadang, 7) Tajulangek dan Tajugambuang, 8) Larangan Mangulai Paku, 9) Batang Lundang, 10) Rawa Menangis, 11) Datuak dan Harimau.